Analisis Kualitas Surat Kabar Online Terbaik Menggunakan Metode Simple Additive Weighting (SAW) - Sianturi, Lydia Shinta Maria; Meliza Gultom; Sertiani Rosida Gultom (Journal of Decision Support System Research, 2024)
This research aims to analyze the quality of the best online newspapers using the Simple Additive Weighting (SAW) method. This method was chosen because of its ability to handle multi-criteria decisions by calculating the preference value of each option based on predetermined criteria. Online newspapers such as The Washington Pos.com, CNN.com, Reuter.com, Merdeka.com, and others are rated based on various factors, including content quality, update speed, and interactivity. CNN.com, Reuter.com, and Merdeka.com received the highest score of 1, while the lowest rating was with a value of 0,085. This research guides readers in choosing a quality online newspaper, as well as providing insight for newspaper managers in their efforts to improve their services. The SAW method has proven to be effective in conducting quality analysis by considering various relevant criteria.